2023
DOI: 10.3390/w15183178
|View full text |Cite
|
Sign up to set email alerts
|

Sorption of Halogenated Anti-Inflammatory Pharmaceuticals from Polluted Aqueous Streams on Activated Carbon: Lifetime Extension of Sorbent Caused by Benzalkonium Chloride Action

Barbora Kamenická,
Tomáš Weidlich,
Miloslav Pouzar

Abstract: The enhancement of the adsorption capacity of activated carbon (AC) using benzalkonium chloride (BAC) within the adsorption of halogenated pharmaceuticals flufenamic acid (flufa) and diclofenac (dcf) was investigated in this study. An adsorption kinetic study was performed to evaluate the adsorption mechanisms. The adsorption mechanism of both drugs on granulated AC as well as saturated AC activated by BAC can be evaluated via pseudo-second kinetic order. The equilibrium adsorption capacity of spent granulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(11 citation statements)
references
References 53 publications
2
9
0
Order By: Relevance
“…The better separation of RB8 using BAC can be caused by the better solubility of BAC in water and thus a better contact of BAC and RB8 dissolved in water. Based on these findings, BAC combines both sufficient aqueous solubility and the removal efficiency of acid halogenated pollutants such as RB8 dye; for more information, see our previous studies [32,44,45].…”
Section: Separation Of Rb8 Based On Ion Exchange Using Ilsmentioning
confidence: 89%
See 4 more Smart Citations
“…The better separation of RB8 using BAC can be caused by the better solubility of BAC in water and thus a better contact of BAC and RB8 dissolved in water. Based on these findings, BAC combines both sufficient aqueous solubility and the removal efficiency of acid halogenated pollutants such as RB8 dye; for more information, see our previous studies [32,44,45].…”
Section: Separation Of Rb8 Based On Ion Exchange Using Ilsmentioning
confidence: 89%
“…Our previous works [32,44,45] reported that the addition of appropriate amounts of quaternary ammonium compounds (R 4 NX, ILs) to the aqueous solutions of acidic halogenated compounds (substituted with -COO − or -SO 3 − groups), including dyes or drugs, results in ion exchange and the formation of respective insoluble ion pairs (see Equation ( 1) above and Scheme 1 below) that can be separated from aqueous solutions by simple filtration. The formation of the mentioned ion pairs has been earlier proven by NMR analysis; see refs.…”
Section: Separation Of Rb8 Based On Ion Exchange Using Ilsmentioning
confidence: 99%
See 3 more Smart Citations